Realitas Masyarakat 5.0 Perspektif Pendidikan Modern KH. Zainuddin Fananie - Darmalaksana, Wahyudin; Ratnasih, Teti (Journal of Innovation Research and Knowledge, 2022)
This study aims to discuss the reality of society 5.0 according to Islam. This study uses a qualitative approach by applying the analytical descriptive method. The formal object of this research is the Islamic view which is manifested by KH. Zainuddin Fananie is related to modern education, while the material object is the reality of society 5.0 for the Indonesian context. The results of research and discussion show that the foundation of modern education KH. Zainuddin Fananie in the form of spirit, mind, and charity has relevance to the idea of society 5.0 whose reality requires change, happiness, and prosperity. This study concludes that the view of modern education KH. Zainuddin Fananie is relevant to be used to shape the reality of society 5.0 in the Indonesian context.